Celastrol promotes apoptotic cell death in thyroid cancer cells through a caspases-dependent pathway - Ruoyi Yang; Jie Yao; Hong Ma; Chunyan Shui; Teng Li; Sicheng Zhang; Chao Li (Thyroid Research)
Abstract Background Celastrol, a naturally occurring bioactive compound, has demonstrated potential in treating inflammation, obesity, and tumors, particularly in colorectal, gastric, and breast cancers. However, its therapeutic effects on thyroid cancer (TC), which have poor clinical outcomes, remain unclear. This study aimed to investigate Celastrol's potential in treating thyroid cancer using cell lines. Methods The viability and proliferation of thyroid cancer cells treated with or without Celastrol were analyzed by CCK-8 and colony formation assay. The state of thyroid cancer cells treated with or without Celastrol were observed by microscopy. Further evidence from flow cytometry and TUNEL staining demonstrated the induction of apoptotic processes in thyroid cancer cells. The expression of PARP1, Caspase-3, Bax, BCL2 in thyroid cancer cells after indicated treatment was analyzed by Western blot and Caspase-3 expression in thyroid cancer cells after 12 and 24 h of Celastrol treatment was detected by immunofuorescence assay. Anaplastic thyroid cancer growth-limiting of Celastrol was evaluated in nude mice. Results Celastrol induction promoted apoptotic in TC cells, increased the expression of PARP1, Bax and Caspase-3 and reduces expression of BCL2 by Western Blot. The expression of Caspase-3 was increased by immunofluorescence, which indicating that Celastrol may serve as an adjuvant therapeutic agent for thyroid cancer treatment by inducing apoptosis through the caspase-3 pathway. Celastrol treatment of mice implanted with anaplastic thyroid cancer cells also inhibited tumor growth, associated with reduced Ki-67 and increased Caspase-3. Conclusions Celastrol promotes apoptotic cell death in thyroid carcinoma cells by the Caspase-3 pathway.